Titanium superoxide: a heterogeneous catalyst for anti-Markovnikov aminobromination of olefins - Shaikh, Tanveer Mahamadali; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2009)
A new facile procedure for the aminobromination of olefins in high yields has been described using p-toluene sulfonamide (p-TsNH(2)) and N-bromosuccinimide (NBS) as introgen and bromine sources, respectively, and titanium superoxide as a truly heterogeneous catalyst. The formation of anti-Markovnikov product exclusively in all the cases studied possibly proceeding I free radical reaction pathway is remarkable. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: anti-Markovnikov addition; Bromoamination; N-Bromosuccinimide; p-Toluenesulfonamide; Titanium superoxide

Two stereocentered HKR of anti-β,β′-diphenylpropanoxirane and anti-3-phenylethyloxiranes catalysed by Co(III)(salen)-OAc complex: enantioselective synthesis of (+)-sertraline and (+)-naproxen - Kamble, Rohit B. (New Journal of Chemistry, 2018)
The Co(III)(salen)OAc-catalyzed two stereocentered hydrolytic kinetic resolution (HKR) of anti-β,β′-diphenylmethyloxirane and anti-3-phenylethyloxiranes affords the corresponding anti-1,2-diols and oxiranes in high enantiomeric excess. The synthetic potential of this methodology is demonstrated by the enantioselective synthesis of (+)-sertraline, an antidepressant drug, and (+)-naproxen, an anti-inflammatory drug.

Ti-superoxide catalyzed oxidative amidation of aldehydes with saccharin as nitrogen source: synthesis of primary amides - Kamble, Rohit B.; Mane, Kishor D.; Rupanawar, Bapurao D.; Korekar, Pranjal; Sudalai, A.; Suryavanshi, Gurunath (RSC Advances, 2020)
A new heterogeneous catalytic system (Ti-superoxide/saccharin/TBHP) has been developed that efficiently catalyzes oxidative amidation of aldehydes to produce various primary amides. The protocol employs saccharin as amine source and was found to tolerate a wide range of substrates with different functional groups. Moderate to excellent yields, catalyst reusability and operational simplicity are the main highlights. A possible mechanism and the role of the catalyst in oxidative amidation have also been discussed.